PENGARUH LINGKUNGAN SEKOLAH YANG MENDUKUNG PERKEMBANGAN EMOSIONAL ANAK BERKEBUTUHAN KHUSUS - Wardana, Marchelino (RELASI: Jurnal Penelitian Komunikasi (e-ISSN: 2807-6818), 2025)
The school environment plays a significant role in supporting the emotional development of children with special needs. This study explores how elements such as social interactions, educational policies, and physical and psychological facilities influence students' emotional well-being. The research focuses on the roles of teachers, peers, and infrastructure in creating a supportive learning atmosphere. Additionally, the study highlights the importance of family and community involvement in fostering a nurturing environment for children's emotional development. Using a qualitative approach, data were collected through observations and in-depth interviews with teachers, students, and parents. The findings indicate that inclusive schools create a safe and welcoming environment that fosters emotional stability and active participation in school activities. Moral and psychological support from teachers and peers emerged as key contributors to boosting students’ self-confidence and social skills. This study emphasizes the need for collaboration among schools, families, and communities in establishing child-friendly environments to holistically nurture the emotional growth of children with special needs.